People's Republic of China-Hong Kong Special Administrative Region : Staff Report for the 1999 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report ;, 2000)
The Asian crisis hit the Hong Kong Special Administrative Region (SAR) economy hard in 1998, despite its generally strong fundamentals. In response to the crisis, the authorities eased fiscal policy-within the framework of a medium plan to restore budget balance, and significantly strengthened job creation and retraining efforts. Despite the inevitable pressures arising from declining output and the regional crisis, the financial position of the banking system remains generally strong. Executive Directors strongly supported the authorities' efforts to further strengthen employment and training programs.